ANALISIS PERANCANGAN E-COMMERCE TART & CAKE FAFA CHEESE BERBASIS WEB - Kusnandar Kusnandar; Ita Arfyanti; Nursobah Nursobah (Jurnal Ilmiah Matrik, 2021)
This study discusses about e-commerce analysis and design at the Fafa Cheese shop. The sales system is still done manually, monthly data reports are still done in recording into a book which can lost sales reports, and there is no price information and tart sold, it is necessary to have the delivery status of the tart sold. The development of this sales information system uses the waterfall development system. This study aims to design an online cake sales application, provide information about prices and cakes sold and provide information that cakes have been sent to customers. The results of this study are the creation of e-commerce design, making it easier to make monthly reports, the availability of price information and cakes sold, and the status of cake delivery if the cake has been sent to the customer.